Characteristics of Microstructure and Fracture Toughness According to the Groove Shape of Submerged Arc Welding - Yong-Taek Shin; Chang-Ju Jung; Seong-Han Bae; Gyubaek An; Myungrak Son; Young-Il Park (Metals, 2024)
This study investigates the effects of heat input on the microstructure and fracture toughness of SAW (Submerged Arc Welding) joints with K-groove and X-groove weld preparations using S460NL steel. Microstructural analysis focused on acicular ferrite, grain boundary ferrite, and MA (Martensite–Austenite) constituents to assess their influence on CTOD (Crack Tip Opening Displacement). The results indicate that the K-groove achieved a higher CTOD value of 0.82 mm compared to 0.13 mm for the X-groove, attributed to differences in microstructural composition and cooling rates. The findings highlight the impact of groove geometry and heat input on weld performance.